Effectiveness of two-dose vs. one-dose varicella vaccine in children in Shanghai, China: a prospective cohort study - Li, Yue; Xu, Fang; Liu, Meiling; Teng, Sashuang; Liang, Fan; Wang, Fei (Frontiers in Public Health, 2024)
Objective Varicella, a highly contagious viral disease caused by the varicella-zoster virus (VZV), affects millions globally, with a higher prevalence among children. After the initial infection, VZV lies dormant in sensory ganglia and has the potential to reactivate much later, causing herpes zoster (HZ). Vaccination is one of the most effective methods to prevent varicella, and the two-dose varicella vaccine (VarV) regimen is widely used around the world. In China, the VarV has been included in the national immunization programme with a recommended single-dose regimen. This study aimed to compare the effectiveness of the two-dose vs. one-dose VarV regimen in children in Shanghai, China. Materials and methods A prospective cohort study was conducted in Shanghai, China, from September 2018 to December 2022. The study enrolled children aged 3–18 years who had received either the one-dose, two-dose, or 0-dose VarV regimen. Vaccination history, varicella infection status, and relevant variables, including demographic information (name, date of birth and sex) and medical history (clinical features of varicella and illness duration) were collected through medical record review and parental interviews. Results A total of 3,838 children were included in the study, with 407 in the 0-dose regimen group, 2,107 in the one-dose regimen group and 1,324 in the two-dose regimen group. The corresponding incidence density in these groups was 0.13, 0.05 and 0.03 cases per 1,000 person-days, respectively. The adjusted vaccine effectiveness (VE) was 81.7% (95%CI: 59.3–91.8%) for the two-dose regimen and 60.3% (95%CI: 29.3–77.7%) for the one-dose regimen, compared to the 0-dose regimen. The two-dose VarV regimen showed a protective effectiveness of 47.6% (95%CI: 2.5–71.9%) compared to the one-dose VarV regimen. Conclusion This study provides evidence supporting the greater effectiveness of the two-dose VarV regimen in preventing varicella infection compared to the one-dose regimen.